2010
DOI: 10.1016/j.ygyno.2009.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Metformin is a potent inhibitor of endometrial cancer cell proliferation—implications for a novel treatment strategy

Abstract: Objectives-Obesity and diabetes are strong risk factors that drive the development of type I endometrial cancers. Recent epidemiological evidence suggests that metformin may lower cancer risk and reduce rates of cancer deaths among diabetic patients. In order to better understand metformin's anti-tumorigenic potential, our goal was to assess the effect of metformin on proliferation and expression of key targets of metformin cell signaling in endometrial cancer cell lines.Methods-The endometrial cancer cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
247
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(267 citation statements)
references
References 38 publications
(54 reference statements)
15
247
3
2
Order By: Relevance
“…Evidence for a proapoptotic effect of metformin is mixed. Cantrell et al 22,28 showed that metformin promoted apoptosis in endometrial carcinoma cells whereas others have been unable to ) or combined metformin and bicalutamide. Using Student's t testing at individual time points revealed significantly reduced tumour growth in the combination group compared with all other groups at days 25 and 27 (*Po0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for a proapoptotic effect of metformin is mixed. Cantrell et al 22,28 showed that metformin promoted apoptosis in endometrial carcinoma cells whereas others have been unable to ) or combined metformin and bicalutamide. Using Student's t testing at individual time points revealed significantly reduced tumour growth in the combination group compared with all other groups at days 25 and 27 (*Po0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that the proapoptotic effect of metformin is only seen when high doses of the drug are utilized. 22 The in vitro model used in these studies did not assess the potential indirect effects of metformin that is, those mediated by inhibition of hyperinsulinaemia. This was more easily assessed using our in vivo xenograft model.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin is a biguanide drug that is widely used as a first-line pharmacological treatment in patients with type 2 diabetes (Cantrell et al 2010). Metformin exerts its effects through the activation of AMPK in muscle, adipose tissue, and liver (Towler & Hardie 2007).…”
Section: Introductionmentioning
confidence: 99%
“…37 Preclinical studies show that metformin inhibits endometrial, ovarian and glioma cells. 34,38,39 Metformin also causes decreased hepatocellular cancer incidence in diabetic patients. 40 In hepatocellular cancer cells, metformin was found to decrease mitochondrial oxygen consumption and suppress hypoxia induced HIF-1 alpha accumulation which was shown to be involved in the development of hepatocellular cancer.…”
Section: Proofs For the Anti-cancerous Activity Of Metforminmentioning
confidence: 99%